A Compact Review of IPMC as Soft Actuator and Sensor: Current Trends, Challenges, and Potential Solutions From Our Recent Work - Hao, Muyu; Wang, Yanjie; Zhu, Zicai; He, Qingsong; Zhu, Denglin; Luo, Minzhou (Frontiers in Robotics and AI, 2019)
Recently, Ionic polymer metal composites (IPMC), becoming an increasingly ionic artificial muscle, are used as soft actuators for its inherent properties of light weight, flexibility, softness, especial efficient transformation from electrical energy to mechanical energy with large bending strain response under low activation voltage. In this paper, we reviewed several defects to restrict IPMC applications, such as non-standardized preparation steps, relaxation under DC voltage, solvent evaporation and low blocking force etc. Corresponding solutions were proposed and developed recently to overcome above mentioned problems. The working mechanism and preparation process of IPMC were firstly clarified. After that, we investigated the main factors which influence the actuating performance of IPMC. We also reviewed the optimization strategies in IPMC actuation, including improving preparation steps, increasing thickness of base membrane and selecting suitable additives in electrolyte layer, replacing water with ionic liquids as solvent, controlling water content and encapsulating etc. Taking into account the role of the interface electrode, the effects of interfacial electrode on the performance of IPMC are revealed based on our previous work. Finally, we also discussed IPMC as sensors theoretically and experimentally. The defect elimination will promote IPMC applications in soft robotics.